2012
DOI: 10.1590/s0482-50042012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Trabalho e potência dos músculos extensores e flexores do joelho de pacientes com osteoartrite e com artroplastia total de joelho

Abstract: Introduction: The infl ammatory manifestations of knee osteoarthritis (OA) lead to muscle inhibition and hypotrophy, resulting in a reduction in total muscle work and muscle power. Total knee arthroplasty (TKA) is the most adequate surgery for the treatment of advanced OA. However, its effects on muscle functional behavior have not been well understood. Objective: To compare the total work and power of the knee fl exor and extensor muscles in patients with OA (20) and in patients post-TKA (12) at two angular v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
8

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
(82 reference statements)
0
3
0
8
Order By: Relevance
“…The joint diseases that most often affect individuals submitted to THA and TKA are the osteoarthrites. 5 , 6 , 13 Piano, Golmia and Scheinberg carried out a study in Brazil and demonstrated that the diagnostic profile of patients reached 92.4% only for osteoarthritis and 2% for inflammatory arthritis. 14 In this study, although the diagnostic classification is more specific, in general the results are similar, but with a higher prevalence of arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The joint diseases that most often affect individuals submitted to THA and TKA are the osteoarthrites. 5 , 6 , 13 Piano, Golmia and Scheinberg carried out a study in Brazil and demonstrated that the diagnostic profile of patients reached 92.4% only for osteoarthritis and 2% for inflammatory arthritis. 14 In this study, although the diagnostic classification is more specific, in general the results are similar, but with a higher prevalence of arthritis.…”
Section: Discussionmentioning
confidence: 99%
“… 5 The arthroplasty provides better quality of life; however, among the possible complications the occurrence of postoperative infection stands out. 6 , 7 This is considered a severe complication due to the morbidity associated with prolonged hospitalization and need for surgical reinterventions and may result in shortening of the affected limb, severe deformities and death. 7…”
Section: Introductionmentioning
confidence: 99%
“…The muscle's total work is the action of strength over a specific distance, i.e, the action of torque during the range of motion. If this value is low, it may suggest that, clinically, the muscle function has changed and that the energy expended during a range of motion is not suitable or has a muscular deficit (36). In addition, the peak torque measures were found to be similar among the study's subjects.…”
Section: Discussionmentioning
confidence: 99%
“…5 A artroplastia proporciona melhor qualidade de vida, contudo, entre as possíveis complicaç ões destaca-se a ocorrência de infecção pós-operatória. 6,7 Essa é considerada uma complicação grave pela morbidade associada ao prolongamento da internação e necessidade de reintervenç ões cirúrgicas e pode culminar no encurtamento do membro afetado, em deformidades graves e óbito. 7 A Agência Nacional de Vigilância Sanitária do Brasil reconhece a importância de aç ões de prevenção e lançou experimentalmente em 2014 o programa para o Registro Nacional de Artroplastias.…”
Section: Introductionunclassified